MODELING AND SIMULATION OF MATRIX CONVERTER FOR WIND POWER GENERATION - Masood, F.; Mahmood, T.; Choudhry, M. A. (The Nucleus, 2013)
In this paper, a matrix converter structure is proposed which is suitable for wind power generation applications. The matrix converter (MC) is the most general converter type in the family of AC-AC converters. It is a single-stage converter which has an array of mÃ—n bidirectional power switches to connect, directly, an m-phase voltage source to an n-phase load. It does not have any DC-link circuit and does not need any large energy storage elements. The key element in a matrix converter is the fully controlled four-quadrant bidirectional switch, which allows high-frequency operation. The proposed converter uses MOSFETs as bidirectional switches. The model has been implemented using MATLAB/SIMULINK. The results obtained are presented. The waveforms for input current and output voltage are sinusoidal with very low total harmonic distortion (THD). Low THD is an indication that the model is suitable for wind power generation applications. The simulation results confirm the reduction of conversion losses by 10% to 12% as compared to conventional two stage converters thereby increasing the overall conversion efficiency. The MOSFETs which have been used as switching devices have four to five times more switching frequency as compared to IGBTs thus improving the resulting wave shapes.